On What Does Rationality Hinge? - Avnur, Yuval (International journal for the study of skepticism, 2017)
The two main components of Coliva’s view are Moderatism and Extended Rationality. According to Moderatism, a belief about specific material objects is perceptually justified iff, absent defeaters, one has the appropriate course of experience and it is assumed that there is an external world. I grant Moderatism and instead focus on Extended Rationality, according to which it is epistemically rational to believe evidentially warranted propositions and to accept those unwarrantable assumptions that make the acquisition of perceptual warrants possible and are therefore constitutive of ordinary evidential warrants. I suggest that, even though Extended Rationality might be true, it cannot do the work that Coliva wants it to do. Although my objections do not show that it is false, they can serve to clarify what sorts of problem a theory of justification or rationality could possibly address. This provides an alternative to Coliva’s view of the skeptical problem and the question, on what does rationality hinge?